(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The well-known embryo transfer matter, which has been regulated by the Court of Rome with an order and the lack of a specific regulation concerning this particular case “by error” and similar particular cases, turns on the debate about the ownership of the filial relationship between “genetic parents” and “biological parents” and the status filiationis definition. By studying the current regulation concerning filiation and using the analogy interpretive tool, the authors examine this particular case making observations about the adequacy of the current regulation concerning such filial relationships, noticing that the filial relationship and the consequent right to personal identity has gradually diversified itsfelf by the naturalistic criterion of genetic membership to stress the voluntary aspect of the behavior meant as responsibility of the procreation and new principle of filiation.